On the automated interactive processing of graphic images of geological and geophysical objects - Starostenko, V. I.; Sharypanov, V. M.; Savchenko, A.S.; Legostaeva, O. V.; Makarenko, I.B.; Kuprienko, P. Ya. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2011)
The principle and stages of work have been stated for the Space Map program destined for loading the computed with geological-geophysical information presented graphically as the bodies (areas, zones) on the paper bearers or as a file of scan pattern. Application of the program facilitates and accelerates the stage of loading information into a computer considerably, and the consequent work as a result, i. e. the file of a program result can be used directly for solving the problems of geophysics.